Desain Lampu Utama Mobil dengan Filter Polarisator sebagai Anti Silau - Mellina Ayu Daynuari; Ayu Amalia; Bayu Setiaji (LPPM UNIVERSITAS PGRI SILAMPARI, 2022)
The lamp is a part that has an important function on the vehicle. The function of this section is to illuminate the road, besides that the use of lights must also provide comfort for the driver, meaning that it does not give a glare effect when used. This glare effect is caused because light has a diffuse nature. Therefore, the use of a polarizing filter can convert the light into polarized light. The purpose of this research is to design an anti-glare product using a polarizing filter. The design will be tested for feasibility through a questionnaire containing polarizer explanation materials, product design drawings, and product assessment statements. The method used in this study is a 4D model using two stages of development, namely define and design. The results of the study in terms of the suitability of the type of lamp used obtained very decent results, the percentage of 84.4%, while in terms of the feasibility of the polarized filter on the lamp obtained very decent results with a percentage of 90.6%. To find out more about the feasibility of the designs made, further research is needed in the form of making products to be tested for feasibility.